P Perbandingan efektivitas cookies dan kapsul daun kelor (moringa oleifera) dalam upaya meningkatkan kadar hemoglobin pada remaja putri anemia - Alwi, Juwitriani; Dahlia, Besse; Ibrahim, Muh. Siddik; Fandir, Abdul; Anwar, Rina; Hurfiati, Hurfiati (Media Gizi Kesmas, 2025)
Background: Iron Deficiency Anemia (IDA) during adolescence can have serious long-term consequences, not only compromising individual health but also increasing the risk of complications during future pregnancies. Local food sources such as moringa oleifera leaves offer a promising strategy to address this issue, given their high iron content. Developing practical, acceptable forms such as cookies and capsules may provide holistic solutions for improving hemoglobin levels. Although both preparations have been shown to significantly enhance hemoglobin levels within the same intervention period, differences in their composition, production methods, and potential iron bioavailability warrant further comparison. Objectives: This study aimed to compare the effectiveness of moringa-based cookies and capsules in improving hemoglobin levels among adolescent girls diagnosed with iron deficiency anemia. Method: A quasi-experimental study was conducted in 2024 among 53 female high school students selected through purposive sampling. Hemoglobin concentrations were measured using the Easy Touch GCHb device. Paired t-tests were used to assess changes within each group, and independent t-tests were applied to compare outcomes between groups. Results: The study proved that the mean hemoglobin level in the moringa cookies group increased to 12.52 g/dL (p=0.002), while the capsule group showed an increase to 12.20 g/dL (p=0.001). However, no significant difference was observed between the two interventions (p=0.412). Conclusion: Both moringa cookies and capsules effectively improved hemoglobin levels in adolescent girls with iron deficiency anemia. Nevertheless, there was no significant difference in the extent of improvement between the two forms of supplementation.